Biologia e ecologia comportamental da vespa eussocial primitiva Mischocyttarus (Megacanthopus) parallelogrammus (Hymenoptera, Vespidae) - Togni, Olga Coutinho [UNESP] (2014)
The social wasps are represented in Brazil by Polistinae, which is arranged in 21 genera divided among the tribes Mischocyttarini, Polistini and Epiponini. The Mischocyttarini tribe represents the largest genus of social wasps, Mischocyttarus, with 245 species distributed in nine subgenres. The species of Mischocyttarus are considered primitive eusocial, of independent foundation and without morphological caste differentiation. The studied species, Mischocyttarus (Megacanthopus) parallelogrammus, is endemic to Brazil, being the objective of this study to conduct a preliminary study involving features of the biology of M. parallelogrammus, in order to cooperate with investigations into the evolution of the eusociality in wasps, by analyzing aspects of the colony cycle, the nest architecture, the labor division, the foraging activity, the dominance hierarchy and the chemical and visual communication of this species. Like in other species, M. parallelogrammus presents foundations and abandonments throughout the year. Abandonment rates are probably related to the wide variety of observed natural enemies, with only 13.89% of the total colonies studied reaching the stage of natural decline. Of the remaining colonies observed, 31.94% were abandoned for unknown reasons, 27.78% were abandoned by the occurrence of parasites or parasitoids, 12.50% were contaminated by fungi and 12.50% were predated. The foundation of the colonies by haplometrosis was predominant (81.94%), even with the foundations of females by association representing greater success. The interval of development of immature M. parallelogrammus appeared greater than other species of the genus, with the average total development time of immatures being 85.20 days. The founders of M. parallelogrammus had an average lifespan of 82.71 ± 53.32 days, 95.81 ± 62.25 days for subordinates and 191.86 ± 91.19 days for dominants. Nests of M. parallelogrammus are attached by a short peduncle...